The Genetic Relationship Between Balinese And Balinese Malay: A Lexicostatistics And Phonemic Correspondence Study - Ida Ayu Putu Aridawati; Temaja, I Gede Bagus Wisnu Bayu; Ida Bagus Rai Putra; I Wayan Tama; I Made Sudiana; I Wayan Sudiartha; I Gusti Ayu Armini (International Journal of Education, Vocational and Social Science, 2023)
This research aimed to explore the genetic relationship between Balinese and Balinese Malay quantitatively and qualitatively. The research was conducted in three steps: 1) data collection, 2) data analysis, and 3) data display. Data collection was conducted by implementing the interview method through a guided interview, recording, and note-taking techniques. The data were 200 Swadesh word lists collected from speakers of both languages as the data. Data analysis was conducted by implementing lexicostatistics and phonemic correspondence techniques. The data were displayed formally and informally, as well as in both combinations. The research results showed that both languages have a 36% genetic relationship percentage. The time between the two languages was presumed to have diverged around 2,354 – 2,157 years ago. It is estimated that both languages started to diverge from their earlier proto-language around 2,569 years ago. In addition, six phonemic correspondences of both languages consist of /ə – a /, / i – ə /, / a – ə /, / o – u /, / u – o /, and / h – r /. Concerning the levels of language classification, the genetic relationship of both languages belongs to a common language family since the results are within the percentage range (36-81%) and diverged year range (500-2,500) years. Based on the genetic language typology, it can be concluded that both languages belong to Austronesian languages. Specifically, they belong to the subfamily Malayo-Sumbawan languages.